Forgiveness, Gratitude, Happiness, and Prosocial Bystander Behavior in Bullying - García-Vázquez, Fernanda Inéz; Valdés-Cuervo, Angel Alberto; Martínez-Ferrer, Belén; Parra-Pérez, Lizeth Guadalupe (Frontiers in Psychology, 2020)
The relationships among character strengths (forgiveness and gratitude), happiness, and prosocial bystander behavior in bullying were analyzed. The sample includes 500 (early adolescents) and 500 (middle adolescents) of both genders, between 12 and 18 years old (M age = 14.70, SD = 1.58). Two structural equation models were calculated. Results of the first model indicated that forgiveness, gratitude, and happiness had a direct positive relation with prosocial bystander behavior. Furthermore, human strengths were indirectly related to prosocial behavior in bullying for this effect in happiness. The second model showed that prosocial bystander behavior had a positive effect on human strengths and happiness. Multigroup analyses indicated that gender and stage of adolescence did not moderate the relations found in the model. Overall findings suggest a reciprocal relationship between character strengths, happiness, and prosocial bystander behavior.